Drosophila Sensory Neurons Require Dscam for Dendritic Self Avoidance and Proper Dendritic Field Organization - Soba, Peter (2007)
A neuron’s dendrites typically do not cross one another. This intrinsic self-avoidance mechanism ensures unambiguous processing of sensory or synaptic inputs. Moreover, some neurons respect the territory of others of the same type, a phenomenon known as tiling. Different types of neurons, however, often have overlapping dendritic fields. We found that Down’s syndrome Cell Adhesion Molecule (Dscam) is required for dendritic self-avoidance of all four classes of Drosophila dendritic arborization (da) neurons. However, neighboring mutant class IV da neurons still exhibited tiling suggesting that self-avoidance and tiling differ in their recognition and repulsion mechanisms. Introducing one of the 38,016 Dscam isoforms to da neurons in Dscam mutants was sufficient to significantly restore self-avoidance. Remarkably, expression of a common Dscam isoform in da neurons of different classes prevented their dendrites from sharing the same territory suggesting that co-existence of dendritic fields of different neuronal classes requires divergent expression of Dscam isoforms.